Soybean Agroindustry Development Strategy in Galang District, Deli Serdang Regency - Susan Novrini; M. Syarif Rafinda (JUMEBIN : Journal of Management, Economics, Business, and Investment, 2025)
Based on the results of the study, it shows that the development of agro-industry in the research area has strength and also has opportunities in the development of soybean agro-industry. For this reason, the strategy that must be implemented in such conditions is the SO (Strengths and Opportunity) strategy. From the results of the internal-external matrix obtained, there are several internal factors (Strengths and Weaknesses) and external factors (Opportunity and Threats) that affect the development of the soybean agroindustry, namely: Internal factors of strength (stengths) consist of : Use of advanced technology, Experience in agro-industrial processing, Increase in the number of production, Products produced have taste advantages, Wide product marketing, Products are recognized by the public, There is a variety of products and prices, Using trademarks, The quality of soybeans is very good, Abundant availability of raw materials. Internal factors of weaknesses consist of: Limited capital, Lack of professional personnel, Strategic processing location, Lack of industrial partnerships, No assistance from the government, Non-durable products, Less strategic processing locations, Processed products are perishable, Business is still on a small scale, Labor is still relatives/family. External factors of opportunity consist of: High prices of processed products, Government support to increase the availability of soybeans, Government attention to agro-industry businesses, Availability of large soybean land, Marketing is not too difficult, Knowing information from competitor products, Products are widely consumed, There is a network of cooperation between institutions, Being able to innovate in processing, Gaining the trust of consumers.